2011
DOI: 10.1371/journal.ppat.1002057
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ubiquitin Ligase MARCH5 Promotes TLR7 Signaling by Attenuating TANK Action

Abstract: The signaling of Toll-like receptors (TLRs) is the host's first line of defense against microbial invasion. The mitochondrion is emerging as a critical platform for antiviral signal transduction. The regulatory role of mitochondria for TLR signaling remains to be explored. Here, we show that the mitochondrial outer-membrane protein MARCH5 positively regulates TLR7 signaling. Ectopic expression or knockdown of MARCH5 enhances or impairs NF-κB-mediated gene expression, respectively. MARCH5 interacts specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][47][48][49][50] Several studies suggest that pre-or perinatal exposure to certain triggers might imprint a state of both dysregulated immune response and mitochondrial dysfunction in the progeny as a result of the integration of basic mitochondrial functions with the immune response and antioxidant defense mechanisms. [51][52][53][54][55] Furthermore, maternal exposure during pregnancy to various pathogens and/or the maternal immune response (fever, inflammation) have been associated with significant increased risk of autism spectrum disorder (ASD). [56][57][58][59] In this regard, gestational exposure to the viral mimetic poly(I:C) in rodents resulted in ASD-like behavioral abnormalities in the progeny, 60 and immune cells from the same animals had OXPHOS deficits still present in adulthood.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][47][48][49][50] Several studies suggest that pre-or perinatal exposure to certain triggers might imprint a state of both dysregulated immune response and mitochondrial dysfunction in the progeny as a result of the integration of basic mitochondrial functions with the immune response and antioxidant defense mechanisms. [51][52][53][54][55] Furthermore, maternal exposure during pregnancy to various pathogens and/or the maternal immune response (fever, inflammation) have been associated with significant increased risk of autism spectrum disorder (ASD). [56][57][58][59] In this regard, gestational exposure to the viral mimetic poly(I:C) in rodents resulted in ASD-like behavioral abnormalities in the progeny, 60 and immune cells from the same animals had OXPHOS deficits still present in adulthood.…”
Section: Figurementioning
confidence: 99%
“…Firstly, MARCH5 regulates mitochondrial fission and fusion [11]. Secondly, MARCH5 affects TLR signalling [14]. It might be assumed that piscine MARCH5 proteins share the original functions of ancestral MARCH5 factor, i.e.…”
Section: Duplicated March5 Genes From Rainbow Trout Show Different Exmentioning
confidence: 99%
“…The balanced regulation of mitochondrial fission and fusion rates contributes to the cellular fitness concerning for example essential mechanisms like Ca 2þ buffering [13]. Recently, it has been shown that human MARCH5 protein positively regulates TLR7 signaling by ubiquitination of TANK (TRAF family member-associated NF-kB activator) [14]. TANK is known as an inhibitor of TLR-dependent NF-kB activation by suppressing the autoubiquitination of the downstream factor TRAF6 (TNF receptorassociated factor 6).…”
Section: Introductionmentioning
confidence: 99%
“…1B) [4]. K48-linked poly-ubiquitination generally targets the substrates for proteasomal degradation, whereas K63-linked poly-ubiquitination modulates non-proteolytic processes including membrane trafficking and signal transduction [5][6][7][8].…”
Section: Ubiquitin and The Ubiquitination Systemmentioning
confidence: 99%